2016
DOI: 10.1371/journal.pone.0153384
|View full text |Cite
|
Sign up to set email alerts
|

Link-Prediction Enhanced Consensus Clustering for Complex Networks

Abstract: Many real networks that are collected or inferred from data are incomplete due to missing edges. Missing edges can be inherent to the dataset (Facebook friend links will never be complete) or the result of sampling (one may only have access to a portion of the data). The consequence is that downstream analyses that “consume” the network will often yield less accurate results than if the edges were complete. Community detection algorithms, in particular, often suffer when critical intra-community edges are miss… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 44 publications
0
26
0
Order By: Relevance
“…6) can significantly improve the quality of the resulting clustering solutions. A computational approach, which could potentially alleviate some of the demand for increased depth has been proposed (EdgeBoost) (Burgess, Adar & Cafarella, 2015) and shown to improve both Louvain and label propagation methods, is a clear candidate for future assessment.…”
Section: Discussionmentioning
confidence: 99%
“…6) can significantly improve the quality of the resulting clustering solutions. A computational approach, which could potentially alleviate some of the demand for increased depth has been proposed (EdgeBoost) (Burgess, Adar & Cafarella, 2015) and shown to improve both Louvain and label propagation methods, is a clear candidate for future assessment.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, attackers might infer an anonymous user through the existence of connections between users. For example, constructing a probability forecasting for edges, multiplicative weighting and min‐flow analytical scheme . The results in Feng et al show that the increases of local connections and clustering coefficient in social network will lead to the accuracy of the link prediction algorithm enhance.…”
Section: Techniques For Big Data Security and Privacymentioning
confidence: 99%
“…We have shown that increase in 3C sampling depth (Figure 6) can significantly improve the quality of the resulting clustering solutions. A computational approach, which could potentially alleviate some of the demand for increased depth has been proposed (EdgeBoost) (Burgess et al, 2015) and shown to improve both Louvain and label propagation methods, is a clear candidate for future assessment.…”
Section: Limitations and Future Workmentioning
confidence: 99%